2021
DOI: 10.3389/feart.2021.705351
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Cycle Dynamic in Continental Late-Carboniferous to Early Permian Basins of Eastern Pangea (Northeastern Massif Central, France)

Abstract: Late Carboniferous to early Permian organic-rich sedimentary successions of late-orogenic continental basins from the northeastern Massif Central (France) coincide with both the Variscan mountain dismantling and the acme of the long-lasting Late Paleozoic Ice Age. Here, we investigate the carbon and nitrogen cycles in the newly dated sedimentary successions of the Decize–La Machine and Autun basins during these geodynamic and climate upheavals. The sedimentary organic matter has been analyzed through Rock-Eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 128 publications
(185 reference statements)
0
10
0
Order By: Relevance
“…However, the nature of these open‐water microorganisms remains unknown, and their future recognition requires methods used in palynology, organic geochemistry and organic petrology, such as fluorescence microscopy and carbon‐isotope spectrometry (see Clausing 1992; Clausing & Boy 2000; Mercuzot et al . 2021). However, next to the autochthonous primary production, we also note that the biotas of the co‐existing terrestrial environments contributed to the trophic structure of the lake ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nature of these open‐water microorganisms remains unknown, and their future recognition requires methods used in palynology, organic geochemistry and organic petrology, such as fluorescence microscopy and carbon‐isotope spectrometry (see Clausing 1992; Clausing & Boy 2000; Mercuzot et al . 2021). However, next to the autochthonous primary production, we also note that the biotas of the co‐existing terrestrial environments contributed to the trophic structure of the lake ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this facies association is attributed to a profundal lake environment in its most distal part, with minimal sediment supply preventing the homogenization of the water column and favoring OM preservation when dysoxic to anoxic conditions are reached (P2a facies association, Table 2, Fig. 7), as evidenced by Mercuzot et al (2021b).…”
Section: Facies Association P2 and P2amentioning
confidence: 99%
“…The Autun Basin has been extensively investigated for its paleontological content (flora and fauna) and its mineral resources (coal, oil and uranium) since the 18 th century, as described by Pruvost (1942), Elsass-Damon 6 (1977) and Marteau (1983). More recently, studies on OM have attempted to characterize the current alteration of fossil-bearing shales (Odin et al 2015a, b), as well as to describe the types of OM found in the sediments, their variations in the stratigraphy, particularly in the main OM-rich levels of the basin, as well as the dynamics of the carbon and nitrogen cycles (Garel et al 2017;Mercuzot et al 2021b).…”
Section: Geological Setting Of the Autun Basinmentioning
confidence: 99%
“…Ongoing efforts to document the basin evolution, palaeogeography, depositional environments, and local to regional climate signals have been hampered by a lack of highprecision radioisotopic ages, preventing the construction of a robust chronostratigraphic framework, and hence precise regional and global correlations (e.g. Müller et al 2006;Izart et al 2012;Garel et al 2017;Lützner et al 2021;Mercuzot et al 2021b). Many correlations across the late Carboniferous to Permian (C-P) European basins still rely on the use of regional stages based on continental biostratigraphy.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…The structural and palaeoenvironmental settings of C-P basins of the northern Massif Central (France, Fig. 1b) have been re-evaluated and documented in a number of recent studies (Beccaletto et al 2015;Ducassou et al 2019;Garel et al 2017;Mercuzot et al 2021aMercuzot et al , 2021bMercuzot et al , 2022Luccisano et al, 2022).…”
Section: Accepted Manuscriptmentioning
confidence: 99%